Equipamiento dotacional para la gestión de los residuos sólidos en la comuna 14 de Santiago de Cali. (2024)
This architectural project stands as a paradigm of sustainable development, masterfully harmonizing environmental, social and economic aspects in an avant-garde and functional design. Through the application of innovative concepts and architectural elements, it has been possible to create a space that transcends conventional limits, becoming a model of inclusion and respect for the environment.